Nonbilharzial squamous cell carcinoma and transitional cell carcinoma with squamous differentiation of the lower and upper urinary tract - Steffen Rausch (Urology Annals, 2012)
Introduction: Urinary tract squamous cell carcinoma and transitional cell carcinoma with squamous differentiation are rare entities. To characterize tumour biology, prognosis, and therapy, we reviewed our data with squamous cell carcinoma (SCC) and transitional cell carcinoma (TCC/SCC). Materials and Methods: We performed a retrospective single-center analysis of 53 patients with SCC and TCC/SCC treated at our urology department from 30.05.1989 to 30.09.2004. Results: SCC was found in 2% (42/1573) of bladder carcinoma and 7% (11/130) of renal pelvis specimen. Stage pT3 was present in 55% of our patients, indicating a tendency to deep muscular invasion. Nodal and distant metastases appeared in 26%. The overall 5-year survival rate was 26% (tumor specific 46%), with a median survival of 10.5 months. We found that three of four patients with pT2N0 bladder carcinoma could be cured by cystectomy. Lymphnode status was identified as a significant prognostic parameter. For renal pelvis carcinoma, median survival was 7.35 months, with an overall 5-year-survival of 30%. Adjuvant therapy modalities were only performed in a minority of cases, although a therapeutic response was often noticed. Conclusions: SCC is characterized by poor prognosis and individual tumor biology. Survival is related to local tumor extension, indicating the necessity of an early radical surgery. To adequately discuss the role of adjuvant therapy on SCC and TCC/SCC further trials are needed.